Chrono-immunotherapy’s current and future optimization strategies: immunotherapy timing in line with the circadian rhythm brings longer survival benefits - Liu, Daiwei; Li, Zhanlin; Cui, Huijuan; Zhang, Hua; Li, Hai; Wu, Xiaoyuan (Frontiers in Immunology, 2026)
Immune checkpoint inhibitors (ICIs) have revolutionized the treatment landscape for malignant tumors such as advanced lung cancer, but their efficacy is limited. In recent years, the circadian rhythm has provided a brand-new optimization strategy for immunotherapy. This perspective article aims to explore the potential mechanisms of the interaction between immunotherapy and circadian rhythms, reviews clinical evidence supporting that “time-of-day receipt of ICIs brings better therapeutic effects”, and conduct an in-depth analysis of the current practical challenges of chrono-immunotherapy. And emphasize the potential of “chrono-immunotherapy” as a valuable therapeutic approach.